Experiential Marketing To Build Customer Loyalty Through Customer Satisfaction In Higher Education - Tri Endang Yani; Diah Cori Kuswardani; Wyati - Saddewisasi; Witjaksono Eko Hartoto; Adijati - Utaminingsh (Universitas Dharma Wacana, 2022)
This study aims to analyze the effect of Experiential Marketing on customer loyalty through customer satisfaction as an intervening variable in universities. The population in this study were students who were still active at the University of Semarang. The data collection technique used is purposive sampling with the criteria of respondents being students who have taken at least the fourth semester. The analytical method used is multiple linear regression and path analyses. The results showed that Experiential Marketing had a positive effect on Customer Satisfaction, Experiential Marketing had no effect on Customer Loyalty and Customer Satisfaction had a positive effect on Customer Loyalty. Meanwhile, based on path analyses, it is known that Customer Satisfaction is able to mediate the effect of Experiential Marketing on Customer Loyalty